Identification and Authentication of Eurycoma longifolia Root Extract from Zingiber officinale rhizome using FTIR Spectroscopy and Chemometrics - Liling Triyasmono; Isni Munisa; Khoerul Anwar; Totok Wianto; Heri Budi Santoso; Abdul Rohman (Indonesian Journal of Chemometrics and Pharmaceutical Analysis, 2021)
Pasak bumi (Eurycoma longifolia) is one of the plants with androgenic effect having high price in the  herbal medicine market. This study was aimed to apply FTIR spectroscopy in combination with  chemometrics for identification and authentication of Eurycoma longifolia root extract (ELRE) from Zingiber officinale rhizome (ZOR). Identification of ELRE was performed by determining the functional groups responsible for infrared absorption, while the authentication of ELRE was carried out by measuring a mixture of ELRE and ZOR with different concentrations (0-100% of ELRE) using FTIR spectroscopy combined with principal component analysis (PCA) for classification between ELRE and ELRE adulterated with ZOR and partial least square regression (PLSR) for quantification of adulterants. The results indicated that ELRE could be identified at  slected fingerprint wavenumbers of 1500 -1300 cm-1, by the presence of several functional groups including O-H, C=O, C=C, C-O, and C-H. PCA could succesfully ELRE and ELRE adulterated with ZOR with a total of 99% varations could be described by two principle componnets. In addition, PLSR using second derivative spectra succesfully predict ZOR levels with coefficient of determination (R2) of 0.993, root mean square error of calibration of 2.563% and root mean square error of cross validation (RMSECV) of 5.057%. The combination of FTIR spectroscopy and chemometrics was an ideal method for identification and authentication of ELRE adulterated with ZOR.